Extended Finite State Machine Model for Translating Quran Reciting Rules and Jawi Language to Braille Code - A. Abualkishik;; K. Omar (Universiti Sains Islam Malaysia, 2024)
This research concerned with reorganize new Braille symbols to represent the vibrations (Reciting Rules) in the Arabic Holy Quran and the script of the Jawi, the aim of this study is building a system that translate the Quran verses to Braille symbols including new vibrations and standardized the Braille symbols for both; the Jawi language and the Quran reciting rules (Ahkam Tajweed). The Reciting rules that concern through this research were limited for the (Noun + Scoon) vibrations, (Meem + Scoon) vibrations, (Lam + Scoon) vibrations (Kalkala) vibration and (Mudd) vibrations. It builds on an existing translation system that combines extended finite state machine with left and right context matching and a set of translation rules. This allows translating the Arabic and Jawi Languages from text to Braille symbols after detect the vibration for the Quran verses. The experiments were successfully done and evaluated for this research. The output for this research was Braille papers that were printed by special equipment (Index Braille Printer).